2018
DOI: 10.1590/1983-21252018v31n108rc
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interaction in Cowpea Lines Using Gge Biplot Method

Abstract: The GGE Biplot method is efficien to identify favorable genotypes and ideal environments for evaluation. Therefore, the objective of this work was to evaluate the genotype by environment interaction (G×E) and select elite lines of cowpea from genotypes, which are part of the cultivation and use value tests of the Embrapa Meio-Norte Breeding Program, for regions of the Brazilian Cerrado, by the GGE-Biplot method. The grain yield of 40 cowpea genotypes, 30 lines and 10 cultivars, was evaluated during three years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 18 publications
4
27
0
Order By: Relevance
“…The presence of significant genotype (G), years (Y, location (L) main effects and genotype by environment (GE) in ANOVA suggests differential responses of the genotypes and the need to identify high yielding and stable genotypes across test environments. Sousa et al, (2018) found similar results for these three sources of variation in cowpea genotypes. The location (L) variation (24%) indicated that the tested locations in this current study were diverse with the largest differences among locations effects causing the most variation in genotype performance.…”
Section: Discussionsupporting
confidence: 63%
“…The presence of significant genotype (G), years (Y, location (L) main effects and genotype by environment (GE) in ANOVA suggests differential responses of the genotypes and the need to identify high yielding and stable genotypes across test environments. Sousa et al, (2018) found similar results for these three sources of variation in cowpea genotypes. The location (L) variation (24%) indicated that the tested locations in this current study were diverse with the largest differences among locations effects causing the most variation in genotype performance.…”
Section: Discussionsupporting
confidence: 63%
“…In line to this Ermiyas [14] has reported the highest contribution (51.6%) of environmental effect for total variance of soybean grain yield. Similarly, Massaine et al [16] in cowpea and Tadesse et al [17] in common bean noticed the highest variation explained by the environmental effect.…”
Section: Additive Main Effects and Multiplicative Interaction Analysimentioning
confidence: 82%
“…It is, therefore, imperative that genotypes should be identified based on detailed understanding of their genotype × environment interaction and multienvironment trials data can serve as guide for the selection of the best genotypes for target environments (Mustapha et al 2014). The GGE-Biplot method is efficient in detecting the genotype by environment interaction and identifying the most stable genotypes and best environment (Heidari et al 2016;Sousa et al 2018). Keeping this in view, the present investigation was carried out with the objective to examine the stability of upcoming soybean varieties developed for NW Himalayan hills of India.…”
Section: Introductionmentioning
confidence: 99%